A Quasi-Experimental Study of Mobile Health Intervention: Measuring the Impact of Android-Based Prenatal Classes on Knowledge and Attitudes of First-Time Mothers in Indonesia - Hernawati, Erni; Hassan, Hafizh Che; Nambiar, Nisha; Hidayati, Sofa Nurul (Jurnal Bidan Cerdas, 2025)
Introduction: Maternal mortality remains a critical global health challenge, with approximately 287,000 pregnancy-related deaths recorded in 2020 (WHO, 2024). In Indonesia, where maternal healthcare access varies significantly, digital interventions may offer scalable solutions. This quasi-experimental study evaluates the effectiveness of an Android-based prenatal education application in improving knowledge and attitudes among first-time mothers in Cimahi, West Java. By comparing app-based learning with traditional methods, we assess whether mobile technology can help bridge gaps in maternal health education and contribute to safer pregnancy outcomes. Methods: This quasi-experimental study involved 120 first-trimester primigravida women (60 intervention, 60 control) in Cimahi City. The independent variable was the use of an Android-based prenatal education application; dependent variables were maternal knowledge and attitudes. Instruments included a validated 20-item knowledge test and a 10-item attitude Likert scale. Data were analyzed using paired and independent t-tests, as well as SmartPLS path modeling.  Results: In the intervention group, knowledge scores increased from 19.8 ± 2.1 to 34.3 ± 2.0, and attitude scores improved from 8.2 ± 1.2 to 13.3 ± 2.8 (p < 0.001). The control group showed smaller, non-significant changes (knowledge: 19.5 ± 2.2 to 21.5 ± 2.6; attitude: 7.3 ± 1.5 to 8.3 ± 1.6). Post-test differences between groups were statistically significant (p < 0.001). Conclusion: The Android-based prenatal education application significantly enhanced the knowledge and attitudes of first-time pregnant women. These findings support the integration of digital education into routine antenatal care services.